Efektivitas Brain GYM dalam Meningkatkan Motorik Halus Pada Anak Tk Usia 6 Tahun - Rizky Dwi Falafiya Putri; Diani Octaviyanti Handajani (Jurnal Ners, 2026)
Fine motor development in early childhood remains a significant issue in education, as many children experience delays in controlling finger and hand movements. This condition makes it difficult for children to write, draw, or perform activities that require eye-hand coordination. The purpose of this study was to analyze the effectiveness of Brain Gym in improving fine motor skills in 6-year-old kindergarten children. This study used a quasi-experimental design with a two-group pretest-posttest approach. The sample consisted of 20 students drawn using total sampling. The research instruments consisted of a questionnaire and a checklist completed before and after the counseling session. The results showed that Brain Gym effectively improved fine motor skills by 35.3%. The paired t-test showed a p-value of 0.000, indicating a statistically significant difference between fine motor scores before and after the Brain Gym intervention in the sample of 6-year-old kindergarten children. This study concluded that Brain Gym was effective in improving fine motor skills in 6-year-old kindergarten children, with an increase of 35.3%. Therefore, it can be concluded that Brain Gym has a significant impact on improving children's fine motor skills